Coronary Vascular Function and Cardiomyocyte Injury: A Report From the WISE-CVD. Issue 12 (December 2020) - AlBadri, Ahmed; Wei, Janet; Quesada, Odayme; Mehta, Puja K.; Xiao, Yi; Ko, Yi-An; Anderson, R. David; Petersen, John; Azarbal, Babak; Samuels, Bruce; Henry, Timothy D.; Cook-Wiens, Galen; et al.
Abstract : Objective: Women with symptoms or signs of myocardial ischemia but no obstructive coronary artery disease (INOCA) often have coronary vascular dysfunction and elevated risk for adverse cardiovascular events. We hypothesized that u-hscTnI (ultra-high–sensitivity cardiac troponin I), a sensitive indicator of ischemic cardiomyocyte injury, is associated with coronary vascular dysfunction in women with INOCA. Approach and Results: Women (N=263) with INOCA enrolled in the WISE-CVD study (Women's Ischemic Syndrome Evaluation–Coronary Vascular Dysfunction) underwent invasive coronary vascular function testing and u-hscTnI measurements (Simoa HD-1 Analyzer; Quanterix Corporation, Lexington, MA). Logistic regression models, adjusted for traditional cardiovascular risk factors were used to evaluate associations between u-hscTnI and coronary vascular function. Women with coronary vascular dysfunction (microvascular constriction and limited coronary epicardial dilation) had higher plasma u-hscTnI levels (both P =0.001). u-hscTnI levels were associated with microvascular constriction (odds ratio, 1.38 per doubling of u-hscTnI [95% CI, 1.03–1.84]; P =0.033) and limited coronary epicardial dilation (odds ratio, 1.37 per doubling of u-hscTnI [95% CI, 1.04–1.81]; P =0.026). u-hscTnI levels were not associated with microvascular dilation or coronary epicardial constriction. Conclusions: Our findings indicate that higher u-hscTnI is associated with coronary vascular dysfunction in women with INOCA. This suggests that ischemic cardiomyocyte injury in the setting of coronary vascular dysfunction has the potential to contribute to adverse cardiovascular outcomes observed in these women. Additional studies are needed to confirm and investigate mechanisms underlying these findings in INOCA. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00832702. Abstract : Supplemental Digital Content is available in the text.